Pengaruh Komunikasi Interpersonal dan Kepuasan Kerja Terhadap Kinerja Guru Sekolah Dasar Guang Ming Seluruh Indonesia - Isomudin Isomudin; Mettadewi Wong; Prita Puspita; Yanah Sucintani; Oey Hannes Widjaya (Dhammavicaya : Jurnal Pengkajian Dhamma, 2021)
Performance at Guang Ming Elementary School appears to be not optimal. Low quality of graduates is still homework to support the success of future education front. This aspect is still an obstacle faced by Guang Ming Elementary School. The objectives of this research are to (1) Analyze The influence between interpersonal communication and the performance of Guang Elementary School teachers Ming throughout Indonesia (2) Analyze the influence between job satisfaction and performance of Guang Ming Elementary School teachers throughout Indonesia (3) Analyze the influence between interpersonal communication and job satisfaction simultaneously towards the performance of Guang Ming Elementary School teachers throughout Indonesia. This research uses Quantitative research method using Cluster Random sampling technique. Based on this technique, the population in this study was Guang Elementary School teachers Ming throughout Indonesia, totaling 102 people. Based on Slovin’s formula, The total sample taken in this research was 81 teachers. Object This research is about the performance of Guang Ming Elementary School teachers throughout Indonesia